MANAJEMEN PENGAWASAN RISIKO DALAM BISNIS BANK SYARIAH - Nursaman Nursaman (Sekolah Tinggi Ekonomi Islam (STEI) Ar-Risalah Ciamis, 2022)
Until now, Islamic banks in running their business cannot be separated from the influence of conventional banking which uses interest in determining their profits. Substantially, there is no relation between conventional banks and Islamic banks, both in systems, principles, values ​​and so on. This journal will provide some information and solutions for risk management in the Islamic banking business. Before stepping into the Islamic banking business, you should carefully consider and calculate some of the risks that will occur later. At the end of writing this journal, the authors conclude that the Islamic banking business is the same as conventional banks in facing risks, except for the risk of interest rates which must be regulated professionally, so as not to threaten the Islamic banking business itself. There are six risks in the Islamic bank business, namely: market risk, liquidity risk, credit risk, legality risk, reputation risk, compliance risk, operational risk, and strategic risk. Even in dealing with all these risks, it has been explained in the Qur'an Surah Al-Haysr (59): 18.